Iodine concentration as a perfusion surrogate marker in oncology: further elucidation of the underlying mechanisms using volume perfusion CT with 80 kVp - Thaiss, Wolfgang Maximilian; Spira, Daniel (European radiology, 2016)
ObjectivesTo assess the value of iodine concentration (IC) in computed tomography data acquired with 80 kVp, as a surrogate for perfusion imaging in hepatocellular carcinoma (HCC) and lymphoma by comparing iodine related attenuation (IRA) with quantitative Volume Perfusion CT (VPCT)-parameters.MethodsVPCT-parameters were compared with intra-tumoral IC at 5 time points after the aortic peak enhancement (APE) with a temporal resolution of 3.5 sec in untreated 30 HCC and 30 lymphoma patients.ResultsIntra-tumoral perfusion parameters for HCC showed a blood flow (BF) of 52.7 ± 17.0 mL/100 mL/min, blood volume (BV) 12.6 ± 4.3 mL/100 mL, arterial liver perfusion (ALP) 44.4 ± 12.8 mL/100 mL/min. Lesion IC 7 sec after APE was 133.4 ± 57.3 mg/100 mL. Lymphoma showed a BF of 36.8 ± 13.4 mL/100 mL/min, BV of 8.8 ± 2.8 mL/100 mL and IC of 118.2 ± 64.5 mg/100 mL 3.5 sec after APE. Strongest correlations exist for VPCT-derived BF and ALP with IC in HCC 7 sec after APE (r = 0.71 and r = 0.84) and 3.5 sec after APE in lymphoma lesions (r = 0.77). Significant correlations are also present for BV (r = 0.60 and r = 0.65 for HCC and lymphoma, respectively).ConclusionsWe identified a good, time-dependent agreement between VPCT-derived flow values and IC in HCC and lymphoma. Thus, CT-derived ICs 7 sec after APE in HCC and 3.5 sec in lymphoma may be used as surrogate imaging biomarkers for tumor perfusion with 80 kVp.Key points• Iodine concentration derived from low kVp CT is regarded as perfusion surrogate • Correlation with Perfusion CT was performed to elucidate timing and histology dependencies • Highest correlation was present 7 sec after aortic peak enhancement in hepatocellular carcinoma • In lymphoma, highest correlation was calculated 3.5 sec after aortic peak enhancement • With these results, further optimization of Dual energy CT protocols is possible
First Online: 17 December 2015
Gesehen am 19.02.2018